Types and internal hydro-geomorphologic variability of mallines (wet-meadows) of Patagonia: Emphasis on volcanic plateaus - Mazzoni, Elizabeth (2013)
"Mallines" (wet-meadows) are Patagonian ecosystems that provide hydric, biological and scenic resources. They develop in landscape locations that are favourable for water concentration. The area of each "mallin" is usually limited to a few, tens, or hundreds of hectares at most, but independently of their size, they present high variability in their internal physiographic characteristics. These are reflected on the vegetation distribution that basically responds to the space and time water distribution in the "mallín", both at the surface as well as across the soil profile. We analyze the internal variability of a "mallín type" and present a conceptual map that illustrates the functional relationships established between four basic elements: geomorphology, hydrology, soils and vegetation, whose interrelationships permitted to differentiate various situations, which may correspond both to different "mallines" and to subunits within the same "mallin".